Shopping destinations and trust – Tourist attitudes: Scale development and validation. (June 2016) - Choi, Miju; Law, Rob; Heo, Cindy Yoonjoung
Abstract: Shopping is one of the oldest tourist activities and commonly accounts for the majority of travel budgets. However, tourists have expressed concerns regarding the risks they face in shopping destinations. Scholars have suggested that trust is a mechanism for reducing the complexity of human behavior in a situation that involves uncertainty. Therefore, the present study aims to investigate the trust of tourists toward shopping destinations. Specifically, the study attempts to develop and validate the measurement properties of a scale, which measures shopping destination trust. The target sample comprised shopping tourists. Via convenience sampling, 708 usable samples were collected in Hong Kong. Subsequently, purification of the measurement scale, assessment of the latent structure, and scale validation were conducted. Results reveal that shopping destination trust consists of nine dimensions. The present research is expected to shed light on potential research topics in the field of shopping tourism. Highlights: The present study investigated shopping destinations and trust – tourist attitudes. This study developed and validated the measurement properties of a scale that measures shopping destination trust. Results reveal that shopping destination trust consists of nine dimensions.